Dynamic of bacterial populations from Cerrado soils - Pereira, João Carlos; Neves, Maria Cristina Prata; Drozdowicz, Adam (Pesquisa Agropecuaria Brasileira, 1999)
Among tropical environments, Cerrados stand out because of its agriculture potencial. Although microorganisms play an important role on soil sustainability and crop production, few information is available on the effects of soil management systems on Cerrado’s microbial ecology. In this study the effects of environmental conditions and soil management practices on bacterial populations were evaluated. Bacterial population densities in soil under native vegetation were variable and diferentiated. Actinomycetes densities varied from 1.7 to 50 X 104 CFU/g dry soil in Sete Lagoas region, Brazil, whereas bacterial populations in both the first and second year of land use were similar and higher than those from soil under native vegetation in the Planaltina region. Soil management practices did not cause strong modifications in the equilibrium among actinomycetes populations obtained from both spores and hyphal. The spore/hypha ratios varied from 1.1 to 5.8. Correlation coefficients among actinomycetes and other bacteria populations were signifficant in soybeans rhizospheres. Results show that soil management practices used for soybean cultivation in Cerrado soils may influence the equilibrium of bacterial populations.